Wage Theft, Economic Conditions, and Market Power: The Case of H-1B Workers - Jed DeVaro; Peter Norlander (Global Labor Organization (GLO), 2021)
This study explores what determines employers' violations of the wage contracts of workers on H-1B temporary work visas, which occur when firms pay those workers below the promised prevailing or "market" wage. A theoretical framework is proposed that predicts more violations during economic downturns, fewer violations when firms have more labor-market power, and more violations by subcontractor firms. Empirical analysis is based on a firm-level matched dataset of wage and hour violations and the firms that sponsor H-1Bs. Higher labor market power, measured by the Herfindahl-Hirschman Index, is associated with fewer violations. Higher unemployment rates and subcontractor firms are associated with more violations. The effects of the unemployment rate and labor market power are amplified in subcontractor firms.
Keywords: J31; J38; J42; J44; 330; wage theft; guest workers; H-1B workers; labor market competition; wage and hour laws; monopsony labor market